Matrix-M adjuvant enhances antibody, cellular and protective immune responses of a Zaire Ebola/Makona virus glycoprotein (GP) nanoparticle vaccine in mice. Issue 16 (7th April 2016) - Bengtsson, Karin Lövgren; Song, Haifeng; Stertman, Linda; Liu, Ye; Flyer, David C.; Massare, Michael J.; Xu, Ren-Huan; Zhou, Bin; Lu, Hanxin; Kwilas, Steve A.; Hahn, Timothy J.; Kpamegan, Eloi; et al.
Highlights: Recombinant Ebola virus glycoprotein nanoparticle vaccine induces B and T cell responses in mice. Matrix-M adjuvant provides significant immune response enhancement. Ebola glycoprotein nanoparticle vaccine protects mice against a lethal Ebola virus challenge. Abstract: Ebola virus (EBOV) causes severe hemorrhagic fever for which there is no approved treatment or preventive vaccine. Immunological correlates of protective immunity against EBOV disease are not well understood. However, non-human primate studies have associated protection of experimental vaccines with binding and neutralizing antibodies to the EBOV glycoprotein (GP) as well as EBOV GP-specific CD4 + and CD8 + T cells. In this report a full length, unmodified Zaire EBOV GP gene from the 2014 EBOV Makona strain (EBOV/Mak) was cloned into a baculovirus vector. Recombinant EBOV/Mak GP was produced in Sf9 insect cells as glycosylated trimers and, when purified, formed spherical 30–40 nm particles. In mice, EBOV/Mak GP co-administered with the saponin adjuvant Matrix-M was significantly more immunogenic, as measured by virus neutralization titers and anti-EBOV/Mak GP IgG as compared to immunization with AlPO4 adjuvanted or non-adjuvanted EBOV/Mak GP. Similarly, antigen specific T cells secreting IFN-γ were induced most prominently by EBOV/Mak GP with Matrix-M. Matrix-M also enhanced the frequency of antigen-specific germinal center B cells and follicular helper T (TFH ) cells in the spleen in a dose-dependent manner. Immunization with EBOV/Mak GP with Matrix-M was 100% protective in a lethal viral challenge murine model; whereas no protection was observed with the AlPO4 adjuvant and only 10% (1/10) mice were protected in the EBOV/Mak GP antigen alone group. Matrix-M adjuvanted vaccine induced a rapid onset of specific IgG and neutralizing antibodies, increased frequency of multifunctional CD4+ and CD8 + T cells, specific TFH cells, germinal center B cells, and persistence of EBOV GP-specific plasma B cells in the bone marrow. Taken together, the addition of Matrix-M adjuvant to the EBOV/Mak GP nanoparticles enhanced both B and T-cell immune stimulation which may be critical for an Ebola subunit vaccine with broad and long lasting protective immunity.